South Africa : Report on the Observance of Standards and Codes - FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This report provides a summary of the level of observance with the financial assessment task force recommendations and recommendations to strengthen observance. South Africa has developed a comprehensive legal structure to combat money laundering. The financial intelligence unit and other supervisory and investigative bodies appear adequately staffed and genuinely committed to implementing the new system. However, many of these measures are new and have not yet been fully put into effect, and all sectors will continue to increase attention and training on antimoney-laundering issues.